Arrhythmogenic response to isoproterenol testing vs. exercise testing in arrhythmogenic right ventricular cardiomyopathy patients. Issue Volume 20:Issue FI 1(2018) (1st February 2018) - Denis, A; Sacher, F; Derval, N; Martin, R; Lim, H S; Pambrun, T; Massoullie, G; Duchateau, J; Cochet, H; Pillois, X; Cheniti, G; Frontera, A; et al.
Abstract: Aims: To compare the arrhythmic response to isoproterenol and exercise testing in newly diagnosed arrhythmogenic right ventricular cardiomyopathy (ARVC) patients. Methods and results: We studied isoproterenol [continuous infusion (45 µg/min) for 3 min] and exercise testing (workload increased by 30 W every 3 min) performed in consecutive newly diagnosed ARVC patients. Both tests were evaluated with regard to the incidence of (i) polymorphic premature ventricular contractions (PVCs) and couplet(s) or (ii) sustained or non-sustained ventricular tachycardia (VT) with left bundle branch block [excluding right ventricular outflow tract VT]; and compared to a control group referred for the evaluation of PVCs without structural heart disease. Thirty-seven ARVC patients (63.5% male, age 38 ± 16 years) were included. The maximal sinus rhythm heart rate achieved during isoproterenol testing was significantly lower compared to exercise testing (149 ± 17 bpm vs. 166 ± 19 bpm, P < 0.0001). However, the incidence of polymorphic ventricular arrhythmias was much higher during isoproterenol testing compared to exercise testing [33/37 (89.2%) vs. 16/37 (43.2%), P < 0.0001]. Interestingly, isoproterenol testing was arrhythmogenic in all 15 patients in whom baseline PVCs were reduced or suppressed during exercise testing. During both isoproterenol and exercise testing, control group presented a low incidence of ventricular arrhythmias compared to ARVC patients (8.1% vs. 89.2%, P < 0.0001 and 2.7% vs. 43.2%, P < 0.0001, respectively). Conclusions: The incidence of polymorphic ventricular arrhythmias is significantly higher during isoproterenol compared to exercise testing in newly diagnosed ARVC patients, suggesting its potential utility for the diagnosis.